2019
DOI: 10.5001/omj.2019.39
|View full text |Cite
|
Sign up to set email alerts
|

Gestational Trophoblastic Disease at Sultan Qaboos University Hospital: Prevalence, Risk Factors, Histological Features, Sonographic Findings, and Outcomes

Abstract: Objectives We sought to assess the prevalence of gestational trophoblastic diseases (GTD) among pregnant women at Sultan Qaboos University Hospital (SQUH) and compare our results with the international studies. We also sought to determine the risk factors, histological features, sonographic findings, and outcomes in women with GTD. Methods We conducted a retrospective cohort study of all women diagnosed with GTD and followed at SQUH between November 2007 and October 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 16 publications
0
7
1
2
Order By: Relevance
“…Regarding the type of lesion in this study, complete moles were most frequent (65.2%). A similar study in Nigeria reported 57.34% complete mole [12], and in another seven-year study in Oman complete hydatidiform mole was reported in 43.8% [14]. However, in our study the second most frequent lesion was invasive mole (20.4%), which is higher than reported in similar regional and international studies (1.46%, 2.7%, 2.56% and 12.5%) [15][16][17][18].…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Regarding the type of lesion in this study, complete moles were most frequent (65.2%). A similar study in Nigeria reported 57.34% complete mole [12], and in another seven-year study in Oman complete hydatidiform mole was reported in 43.8% [14]. However, in our study the second most frequent lesion was invasive mole (20.4%), which is higher than reported in similar regional and international studies (1.46%, 2.7%, 2.56% and 12.5%) [15][16][17][18].…”
Section: Discussionmentioning
confidence: 80%
“…Age analysis in this study revealed that overall, most patients were between 21-30 years of age (41.4%). Related studies in Pakistan and India showed the same age group to have a high prevalence (54.54% and 66%), however international studies reported a high prevalence in 31-40 years of age [14][15][16][17][18]. This is an important finding which shows that a much younger population is affected in this part of the world.…”
Section: Discussionmentioning
confidence: 99%
“…En la mola completa la imagen típica de "copos de nieve" o "panal de abejas" se manifiesta por la cavidad ocupada por ecos disminuidos en amplitud, que corresponden al tejido trofoblástico proliferado [9]. Dentro de los estudios de laboratorio la determinación cuantitativa de la subunidad beta de hCG con valores elevados [10], el estudios histopatológicos tiene una apariencia típica de una masa voluminosa de estructuras de vellosidad coriónica anormales se lo utiliza como el método confirmatorio [11]. El legrado aspirativo previa dilatación cervical mecánica y bajo guía ecográfica es el método de preferencia.…”
Section: Discussionunclassified
“…Pada penelitian di RS Pendidikan Universitas Sultan Qaboos disimpulkan bahwa riwayat multiparitas menjadi salah satu faktor risiko yang signifikan terhadap pembentukan TTG. 13 Pada Huanca-Llamo dkk. dalam uji bivariat disimpulkan bahwa abortus (OR 6,54; 95% CI 3,12 -13,74; p <0,001) dan multiparitas (OR 3,35; CI 95%: 1,47 -7,65; p <0,001) signifikan menjadi faktor risiko PTG.…”
Section: Pembahasanunclassified